Eat Me If You Can: Cognitive Mechanisms Underlying the Distance Effect - Junghans, Astrid F. (Public Library of Science, 2013)
Proximal objects provide affordances that activate the motor information involved in interacting with the objects. This effect has previously been shown for artifacts but not for natural objects, such as food. This study examined whether the sight of proximal food, compared to distant food activates eating-related information. In two experiments reaction times to verbal labels following the sight of proximal and distant objects (food and toys) were measured. Verbal labels included function words that were compatible with one object category (eating and playing) and observation words compatible with both object categories. The sight of food was expected to activate eating-related information when presented at proximity but not at distance, as reflected by faster reaction times to proximal than distant compatible eating words and no difference between reaction times to proximal and distant food for observation words (Experiment 1). Experiment 2 additionally compared the reaction times to wrapped and unwrapped food. The distance effect was expected to occur only for unwrapped food because only unwrapped food is readily edible. As expected, Experiment 1 and 2 revealed faster responses to compatible eating words at proximity than at distance. In Experiment 2 this distance effect occurred only for readily edible, unwrapped food but not for wrapped food. For observation words no difference in response times between the distances was found. These findings suggest that the sight of proximal food activates eating-related information, which could explain people’s differential behavioral responses to reachable versus distant food. The activation of eating-related information upon sight of accessible food could provide a cognition-based explanation for mindless eating.